ANALISIS REGRESI LOGISTIK ORDINAL MENGENAI FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDIKAN ANAK DI DESA SAYANG-SAYANG - Baiq Dewi Kusuma Ananda; Zulmi Insani; Baiq Rika Ayu Febrilia; Dwi Utami Setyawati (Diponegoro University, 2020)
The economic condition of the parents and their level of education are the determining factors for the level of education of the children. The purpose of this study was to analyze the factors affecting the level of education of children (socioeconomic status of parents and parents' latest education). The subjects in this study were 100 people of Sayang-Sayang Village who were determined by simple random sampling technique. Data collection was carried out online using a survey sheet or questionnaire developed with the help of Google Form. The method in analyzing this causal relationship uses ordinal logistic regression analysis. The results showed that the ordinal logistic regression analysis provided two logit models, in which socioeconomic status had a significant effect on the child's education level, while the parents' last education level did not have a significant effect on the child's education level. The first logit model is a logit model that explains the causal relationship between socioeconomic status and the last level of education of high-category children, while the second model is for the middle category level. Research is expected to be one of the references both in the use of ordinal logistic regression and in observing the factors that affect the level of children's education.